The Relationship Between Math Anxiety and Self-Efficacy on the Basic Mathematical Ability of Prospective Elementary School Teachers - Lintang Analisa Ekasari; Fery Muhamad Firdaus; Anwar Senen (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to analyze the relationship between math anxiety and self-efficacy on the basic mathematical abilities of prospective elementary school teachers. The study used a correlational quantitative approach with 282 students from five state universities in Indonesia. The instruments consisted of a math anxiety scale, a self-efficacy scale, and a basic mathematical ability test, all of which had been tested for validity and reliability. Descriptive analysis results show that self-efficacy is in the high category (M = 70.44; SD = 11.21), math anxiety is in the moderate category (M = 29.35; SD = 6.33), and basic mathematical ability is in the good category (M = 19.04; SD = 3.69). Pearson's correlation analysis revealed that self-efficacy was negatively and significantly related to math anxiety (r = –0.436, p < 0.001) and positively related to basic mathematical ability (r = 0.304, p < 0.001). Meanwhile, math anxiety had a weak negative relationship with basic mathematical ability (r = –0.175, p = 0.003). Multiple linear regression results show that self-efficacy has a significant effect on basic mathematical ability (β = 0.281, p < 0.001), while math anxiety has no significant effect (β = –0.053, p = 0.402), with a model contribution of 9.5% (R² = 0.095). Math anxiety is negatively correlated with basic mathematical ability but becomes non-significant when self-efficacy is included in the regression model, indicating an indirect effect. These findings emphasize the importance of strengthening self-efficacy in teacher education to improve prospective elementary school teachers’ mathematical competence.